1999
DOI: 10.1037/0022-0663.91.3.415
|View full text |Cite
|
Sign up to set email alerts
|

The double-deficit hypothesis for the developmental dyslexias.

Abstract: The authors propose an alternative conceptualization of the developmental dyslexias, the double-deficit hypothesis (i.e., phonological deficits and processes underlying naming-speed deficits represent 2 separable sources of reading dysfunction). Data from cross-sectional, longitudinal, and cross-linguistic studies are reviewed supporting the presence of 2 singledeficit subtypes with more limited reading impairments and 1 double-deficit subtype with more pervasive and severe impairments. Naming-speed and phonol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

151
1,428
10
114

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,456 publications
(1,749 citation statements)
references
References 162 publications
151
1,428
10
114
Order By: Relevance
“…Furthermore, language and language-based deficits can be divided into semantic and syntactic deficits (like vocabulary deficits) and phonological deficits, but a double-deficit hypothesis has also been introduced. The double-deficit hypothesis suggests the existence of three subtypes of reading disability: phonological deficits (like phonological awareness and letter-sound decoding), a rapid naming deficit that disrupts orthographic processing and reading speed, or both of the aforementioned types of deficits (Bowers & Wolf, 1993;Wolf & Bowers, 1999;Wolf et al, 2000). Rapid automatized naming (RAN) is a task of naming a series of familiar items as quickly as possible (Denckla & Rudel, 1976).…”
Section: Cognitive Profile and Characteristics Of Dyslexiamentioning
confidence: 99%
“…Furthermore, language and language-based deficits can be divided into semantic and syntactic deficits (like vocabulary deficits) and phonological deficits, but a double-deficit hypothesis has also been introduced. The double-deficit hypothesis suggests the existence of three subtypes of reading disability: phonological deficits (like phonological awareness and letter-sound decoding), a rapid naming deficit that disrupts orthographic processing and reading speed, or both of the aforementioned types of deficits (Bowers & Wolf, 1993;Wolf & Bowers, 1999;Wolf et al, 2000). Rapid automatized naming (RAN) is a task of naming a series of familiar items as quickly as possible (Denckla & Rudel, 1976).…”
Section: Cognitive Profile and Characteristics Of Dyslexiamentioning
confidence: 99%
“…More recently, others have suggested that in addition to phonology, naming speed constitutes an independent and additive source of variance in early reading skills (e.g., Wolf & Bowers, 1999). In a recent meta-analysis, Swanson, Trainin, Necoechea, and Hammill (2003) examined the association between phonological awareness, rapid automatized naming (RAN), reading, and related abilities in a set of 49 independent samples.…”
Section: Introductionmentioning
confidence: 99%
“…Adult dyslexic individuals have also shown impairments in phonological awareness and rapid naming (Felton, Naylor, & Wood, 1990), and it is likely that these variables reflect genuine impairments, as opposed to some form of developmental delay. It can also be argued that phonological awareness and rapid naming represent distinctly different cognitive components underlying reading (Wolf & Bowers, 1999, giving rise to different subtypes of adult dyslexia.Although the heterogeneity of dyslexic populations has supported the separation of dyslexic subtypes, in many cases the evidence has been purely empirical and has lacked theoretical grounding. One theoretical approach comes from models of word recognition.…”
mentioning
confidence: 99%